Auto-silent mode application for mosque using geofencing technique / Mohamad Firdaus Samsudin - Samsudin, Mohamad Firdaus (Faculty of Computer and Mathematical Sciences, 2017)
Mobile device has become as an important part in human life. It offered many functionalities to the human that cannot be denied. However, there are growing concern about the disturbance cause by mobile phones. So, one of the concern is the disturbance from ringing sound at a place that require silence such as at the mosque. Mosque is the place where need a calm environment as Muslim’s people find the serenity and worship to Allah. This disturbance occurred because of sometimes some people forget to turn their phone into silent mode before entering mosque. Therefore, for this final project propose an auto-silent mode application for mosque using geofencing technique. In order to develop this project there are 5 phases that require to fulfil which are information gathering, analysis, design, development and testing known as waterfall model. Geofencing technique is used to detect virtual boundary that have been created. So, when the user enters or exit the virtual boundary it will automatic silent or unsilent the phone. Based on the survey conducted to 100 respondents, 91% from 100 respondents satisfied with the interface of the project and the functionalities of the application. While 85% from 100 respondents agree with the accuracy of Global Positioning System (GPS). As the conclusion, by developing this project it can avoid the disturbance in mosque that cause by mobile phones with it will automatic silent the phone when the people enter the mosque and vice versa.